Mongolčuud, Nėn ėrtnėės XII zuuny ėhėn Talyn nüüdėlčdijn ulamžlal - Ėrdėnėbat, Ulambajaryn; Ėnhbat, Roozongijn (MONSUDAR hėvlėlijn gazar, 2018)
Pictorial history of the Mongols and Mongolia, from antiquity to the beginning of the 12th century
Keywords: Mongols / History / To 1500 / Pictorial works; Xiongnu (Asian people) / History / Pictorial works; Xianbei (Asian people) / History / Pictorial works; Ruanruan (Asian people) / History / Pictorial works; Turkic peoples / History / To 1500 / Pictorial works; Khitan (Chinese people) / History / Pictorial works; Mongols / Histoire / Jusqu'à 1500 / Ouvrages illustrés; Xiongnu (Peuple d'Asie) / Histoire / Ouvrages illustrés; Kitan (Peuple d'Asie) / Histoire / Ouvrages illustrés; Mongolen; Kitan; Nomade; Turkvölker; Xiongnu; Mongolia / History / To 1500 / Pictorial works; Asia, Central / History / To 1500 / Pictorial works; Mongolie / Histoire / Jusqu'à 1500 / Ouvrages illustrés; Asie centrale / Histoire / Jusqu'à 1500 / Ouvrages illustrés